SQUAMOUS CELL CARCINOMA OF THE CONJUCTIVA-CASE REPORT - Markovska, Vesna Celeva; Pandilov, Stefan (Journal of Morphological Sciences, 2022)
Presentation of a patient with a squamous cell carcinoma of the conjunctiva on his left eye. A 83-year â€“old man with a squamous cell carcinoma of the conjunctiva was examined and treated at the University Eye Clinic in Skopje, by the ophthalmologist, after a ophthalmological examination and observation in the small country side-ophthalmology department for a year. Near the temporal limbus at 3 oâ€™clock there was present nodous and white tumorous lesion around 1,4 cm. weath with elevation from the eye surface of 0,5 cm. Around the tumor there was local vascularization.  External photographs were taken to document the lesion. The excision biopsy was performed. Topical antibiotic-steroid combination of eye drops was applied 3 times daily for 4 weeks after the primary excision of tumor. The diagnosis was pathohistologically confirmed at the Institute of Pathology in Skopje. Conclusion : Primary excision biopsy is preferably therapy and treatment. Also the primary excision biopsy is a golden standard for proper diagnosis for small squamous cell carcinoma of conjunctiva.Keywords: squamous cell carcinoma, conjunctiva, eye, pathohistology. Keywords: squamous cell carcinoma, conjunctiva, eye, pathohistology.